Measurement of Noradrenaline and Serotonin Metabolites With Internal Jugular Vein Sampling: An Indicator of Brain Monoamine Turnover in Depressive Illness and Panic Disorder - Esler, Murray; Alvarenga, Marlies; Barton, David; Jennings, Garry; Kaye, David; Guo, Ling; Schwarz, Rosemary; Lambert, Gavin (Frontiers in Psychiatry, 2022)
In research spanning three decades we have measured human brain monoamine turnover, with sampling from the internal jugular veins and measurement of plasma monoamine and metabolite concentration gradients across the brain, This research has drawn on the expertise of the Baker Institute Human Neurotransmitter Research Laboratory and the affiliated research cardiac catheterisation laboratory of the Alfred Hospital. Here we report brain noradrenaline and serotonin turnover in patients with major depressive illness (MDD) and panic disorder (PD). Brain noradrenaline turnover was derived from the combined flux into the internal jugular veins of the metabolites dihydroxyphenylglycol (DHPG) and 3-hydroxy-4-methoxyphenylglycol (MHPG), and brain serotonin turnover from the outflow of the primary metabolite, 5-hydroxyindole acetic acid (5HIAA). Comparison measurements were made in matched healthy research participants. Brain venous sinus scans were also performed, allowing identification of which internal jugular vein drained primarily the cerebral cortex (commonly the right vein) and which drained subcortical regions (commonly the left). In both MD and PD patients brain noradrenaline turnover did not differ from that of healthy participants. In contrast, in both patient groups estimated brain serotonin turnover was increased 3-4 fold (P<0.01). The increase in serotonin release in both MDD and PD was in both cortical, and subcortical brain regions. This neurotransmitter abnormality was normalized in MDD and PD in clinical remission, during selective serotonin reuptake blocker (SSRI) dosing. Interpretation We cannot be sure if the increases in brain serotonin turnover in MDD and PD are causal, or a correlate. The measurements in PD were not made during a panic attack. The increased serotonin turnover here may possibly be a substrate for panic attacks; studies in experimental animals have demonstrated the importance of serotonergic raphe nuclei in anxiety responses. It is puzzling that the brain neurotransmitter abnormality demonstrated was identical in MDD and PD, although it may be pertinent that these psychiatric diagnoses are commonly comorbid. Patient selection criteria minimized comorbidity here. Could increased brain serotonin release be driving the sympathetic nervous activation present in these two disorders, persistent sympathetic activation in MDD and episodic sympathetic activation in PD during panic attacks, which contribute to cardiovascular risk?